(untitled) (Stato, Chiese e pluralismo confessionale, 2025)
The Role of religions in peacebuilding: The enduring legacy of the encyclical Pacem in terris Religions have always played a central role in peacebuilding processes. In this context, the pontifical magisterium of John XXIII acquired particular significance, especially through the encyclical Pacem in Terris, published in 1963 in a period marked by intense international tensions. The document affirms principles such as the dignity of the person, fundamental rights and duties, and cooperation among peoples. This contribution aims to analyse whether, and to what extent, such principles have been received and further developed in subsequent pontifical magisteria, and the impact they have had on the relationship between religious denominations and state legal systems. From the analysis of magisterial texts and normative sources at both Italian and international levels, a growing juridical recognition emerges of the public relevance of religions in promoting “positive peace”. Particular attention is devoted to the Italian constitutional system and to the evolution of international law in the field of peacebuilding. SOMMARIO: 1. La religione tra conflitti e pace - 2. La pace possibile nella Pacem in terris - 3. Il dialogo come metodo - 4. Verso un nuovo umanesimo - 5. La Pacem in terris di fronte alle sfide contemporanee.